Conductive silver paste and preparation method thereof

By introducing gallium-based liquid metal-based composite functional materials, conductive polymers and small-layer two-dimensional materials into the conductive silver paste, the problems of conductive layer failure and interface mismatch in flexible printing are solved, and conductive silver paste with high bending resistance and strong adhesion are achieved, which significantly improves the service life of the equipment and the stability of the electrical connection.

CN119626627AActive Publication Date: 2025-03-14XIAN RARE METAL MATERIALS RES INST CO LTD

Patent Information

Application Number
CN202510150365.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-03-14
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

Currently, during the service process of domestic conductive silver paste for flexible printing, there are problems of conductive layer failure and interface mismatch caused by mechanical deformation and strain such as repeated bending/stretching, resulting in unstable electrical connections and even equipment failure.

Method used

Using a conductive silver paste including conductive silver powder, gallium-based liquid metal-based composite functional material, organic resin bonding phase, curing agent, organic solvent and auxiliary agent, the self-flow crack repair function of gallium-based liquid metal and the interface wetting of conductive polymer and small-layer two-dimensional material is improved to form a conductive layer with high bending resistance and strong adhesion.

Benefits of technology

It significantly improves the service life and electrical connection stability of conductive silver paste, reduces the risk of equipment failure, and solves the problems of conductive layer failure and interface mismatch.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626627A_ABST
    Figure CN119626627A_ABST
Patent Text Reader

Abstract

The invention provides conductive silver paste and a preparation method thereof, and relates to the technical field of electronic paste. The conductive silver paste comprises conductive silver powder, a gallium-based liquid metal-based composite functional material, an organic resin binding phase, a curing agent, an organic solvent and an auxiliary agent, wherein the conductive silver powder is 55-75 parts by weight; the weight part of the gallium-based liquid metal-based composite functional material is 5-25; the weight part of the organic resin binding phase is 4-10; the weight part of the curing agent is 1-3; the weight part of the organic solvent is 2-10; the weight part of the auxiliary agent is 0.1-10 parts; the gallium-based liquid metal-based composite functional material comprises gallium-based liquid metal, a conductive polymer and a few-layer two-dimensional material, wherein the gallium-based liquid metal comprises one or more of gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy; the conductive polymer comprises one or more of polypyrrole, polydopamine or polyaniline; the few-layer two-dimensional material comprises graphene or transition metal carbide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of electronic pastes, and in particular to a conductive silver paste and a preparation method thereof. Background Art

[0002] Conductive silver paste has become one of the commonly used representative functional electronic pastes in the field of flexible electronic printing due to its advantages such as high conductivity, high oxidation resistance and high stability. However, during the service life of domestic flexible printing conductive silver paste, there are problems of conductive layer failure and interface mismatch caused by mechanical deformation strain such as repeated bending / stretching, which can easily lead to unstable electrical connections and even equipment failure.

[0003] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0004] The present invention provides a conductive silver paste and a preparation method thereof, which can improve problems such as conductive layer failure and interface mismatch, improve electrical connection stability, and reduce the risk of equipment failure.

[0005] According to one aspect of the present disclosure, a conductive silver paste is provided, the conductive silver paste comprising the following components: conductive silver powder, gallium-based liquid metal-based composite functional material, organic resin bonding phase, curing agent, organic solvent and auxiliary agent, wherein: the weight portion of the conductive silver powder is 55-75 parts; the weight portion of the gallium-based liquid metal-based composite functional material is 5-25 parts; the weight portion of the organic resin bonding phase is 4-10 parts; the weight portion of the curing agent is 1-3 parts; the weight portion of the organic solvent is 2-10 parts; the weight portion of the auxiliary agent is 0.1-10 parts; The gallium-based liquid metal-based composite functional material includes gallium-based liquid metal, conductive polymer and few-layer two-dimensional material, wherein the gallium-based liquid metal includes one or more of gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy; the conductive polymer includes one or more of polypyrrole, polydopamine or polyaniline; the few-layer two-dimensional material includes graphene or transition metal carbide.

[0006] In an exemplary embodiment of the present disclosure, the conductive silver powder includes silver nanowires, flaky metal silver powder and nano-spherical silver powder, and the silver nanowires are synthesized by a polyol method.

[0007] In an exemplary embodiment of the present disclosure, the organic resin binder phase is one or more of a hydroxyl-terminated polyester resin, an epoxy-modified acrylic resin, and a polyurethane resin.

[0008] In an exemplary embodiment of the present disclosure, the curing agent is a blocked isocyanate curing agent.

[0009] In an exemplary embodiment of the present disclosure, the organic solvent includes two or more of xylene, alkylbenzene, butyl carbitol, terpineol, N-methylpyrrolidone, butyl carbitol acetate and mixed dibasic esters.

[0010] In an exemplary embodiment of the present disclosure, the auxiliary agent includes two or three of modified urea, polysiloxane and a thixotropic agent.

[0011] According to one aspect of the present disclosure, a method for preparing a conductive silver paste is provided, which is used to prepare any one of the conductive silver pastes described above, and the preparation method comprises: Prepare a gallium-based liquid metal-based composite functional material, wherein the gallium-based liquid metal-based composite functional material comprises a gallium-based liquid metal, a conductive polymer and a few-layer two-dimensional material, wherein the gallium-based liquid metal comprises one or more of gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy; the conductive polymer comprises one or more of polypyrrole, polydopamine or polyaniline; the few-layer two-dimensional material comprises graphene or transition metal carbide; The silver nanowire dispersion was prepared by polyol synthesis method; Weighing an organic resin binder phase and an organic solvent by weight, adding them to the silver nanowire dispersion, and stirring until a homogeneous state to form an organic carrier; Adding the gallium-based liquid metal-based composite functional material, flaky metal silver powder and nano-spherical silver powder into the organic carrier in small amounts and repeatedly, and continuing to stir in a planetary mixer to prepare a uniform slurry; Adding an auxiliary agent and a curing agent to the uniform slurry, and continuing stirring to adjust the viscosity and thixotropic properties of the slurry to form an initial conductive silver slurry; The fineness of the initial conductive silver paste is adjusted by a three-roll mill, and the target conductive silver paste is obtained after double-layer filtration.

[0012] In an exemplary embodiment of the present disclosure, the preparation of a gallium-based liquid metal-based composite functional material comprises: Weigh gallium-based liquid metal by weight and add it into a special ultrasonic crushing vessel containing 10 ml of sodium dodecylbenzene sulfonate aqueous solution, and crush it by ultrasonic at a constant temperature of 20° C. to form a suspension 1; Ti3AlC2 powder and lithium fluoride powder were weighed by weight and added into hydrochloric acid solution. The dark green few-layer Ti3C2T x A dispersed aqueous solution of nanosheets is used as suspension II; The suspension 1 and the suspension 2 were mixed by weight and ultrasonicated for 10 minutes. x The electrostatic repulsion between the liquid metal and the gallium-based liquid metal results in a uniform mixed solution of the two-dimensional material. Adding the reactant conductive polymer monomer-polypyrrole to the mixed solution, mixing and stirring, adding the oxidant ferric chloride hexahydrate, and fully reacting for 1 hour to obtain a black suspension; The black suspension is washed multiple times, vacuum filtered and vacuum dried to obtain a gallium-based liquid metal-based composite functional material.

[0013] In an exemplary embodiment of the present disclosure, the polyol synthesis method is used to prepare a silver nanowire dispersion, comprising: 0.3 parts of sodium chloride, 1.2 parts of silver nitrate and 1.2 parts of polyvinyl pyrrolidone were added into a reaction kettle containing ethylene glycol, and a silver nanowire dispersion was prepared by microwave reaction at 140°C.

[0014] In an exemplary embodiment of the present disclosure, the curing agent is a blocked isocyanate curing agent; the organic solvent includes two or more of xylene, alkylbenzene, butyl carbitol, pineol, N-methylpyrrolidone, butyl carbitol acetate and mixed dibasic esters; the auxiliary agent includes two or three of modified urea, polysiloxane and thixotropic agent; the organic resin bonding phase is one or more of hydroxyl-terminated polyester resin, epoxy-modified acrylic resin and polyurethane resin.

[0015] The conductive silver paste and its preparation method disclosed in the present invention significantly improve the application performance of the conductive silver paste in the field of flexible electronic printing by incorporating gallium-based liquid metal-based composite functional materials, especially in solving the problems of conductive layer failure and interface mismatch caused by mechanical deformation such as repeated bending / stretching. For example, the gallium-based liquid metal (such as gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy) in the gallium-based liquid metal-based composite functional material is used as a self-flowing crack repair agent. Its high conductivity and self-healing properties can quickly repair cracks when the silver paste layer is bent or stretched, thereby greatly extending the service life of the conductive silver paste. The addition of conductive polymers (such as polypyrrole, polydopamine or polyaniline) and few-layer two-dimensional materials (such as graphene or transition metal carbides) effectively improves the interface wettability between liquid metal particles and conductive silver powder and substrates. The high flexibility and good interface compatibility of these materials can enhance the matching of rigid and flexible interfaces, which helps to improve the repair effect. At the same time, the conductive polymers and two-dimensional materials in the gallium-based liquid metal-based composite functional materials can also form additional conductive channels, which helps to enhance the stability and reliability of the conductive network. In addition, by precisely controlling the weight of each component in the present disclosure, the conductive silver paste can achieve good adhesion and processing performance while maintaining high conductivity. The synergistic effect of the organic resin adhesive phase, curing agent and additives ensures that the silver paste can form a dense and uniform conductive layer after curing, so that the final conductive silver paste not only has high bending resistance and strong adhesion, but also shows high reliability, effectively solving the conductive layer failure and interface mismatch problems caused by mechanical deformation (such as cracks) in flexible electronic printing.

[0016] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.

[0018] Figure 1 Flow chart of the method for preparing conductive silver paste in the embodiment of the present disclosure.

[0019] Figure 2 The few-layer Ti3C2T in the embodiment of the present disclosure x Scanning electron microscopy image of the nanosheets.

[0020] Figure 3This is a scanning electron microscope image of the gallium-based liquid metal-based composite functional material in the embodiment of the present disclosure.

[0021] Figure 4 This is a scanning electron microscope image of the distribution of gallium elements in the gallium-based liquid metal-based composite functional material in the embodiment of the present disclosure.

[0022] Figure 5 This is a scanning electron microscope image of the distribution of tin elements in the gallium-based liquid metal-based composite functional material in the embodiment of the present disclosure.

[0023] Figure 6 This is a scanning electron microscope image of the distribution of titanium elements in the gallium-based liquid metal-based composite functional material in the embodiment of the present disclosure.

[0024] Figure 7 This is a scanning electron microscope image of the distribution of nitrogen elements in the gallium-based liquid metal-based composite functional material in the embodiment of the present disclosure.

[0025] Figure 8 This is the X-ray photoelectron spectrum of the gallium-based liquid metal-based composite functional material in the embodiment of the present disclosure.

[0026] In the figure: 1. Few-layer Ti3C2T x Nanosheets; 2. Gallium-based liquid metal-based composite functional materials. DETAILED DESCRIPTION

[0027] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that this disclosure will be comprehensive and complete and will fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted.

[0028] Although relative terms such as "upper" and "lower" are used in this specification to describe the relative relationship of one component of the illustration to another component, these terms are used in this specification only for convenience, such as according to the orientation of the examples described in the drawings. It is understood that if the device of the illustration is turned upside down, the component described as "upper" will become the component "lower". When a structure is "on" other structures, it may mean that the structure is formed integrally on the other structure, or that the structure is "directly" disposed on the other structure, or that the structure is "indirectly" disposed on the other structure through another structure.

[0029] The terms "a", "an", "the" and "said" are used to indicate the presence of one or more elements / components / etc.; the terms "comprising" and "having" are used to indicate an open-ended inclusive meaning and mean that additional elements / components / etc. may be present in addition to the listed elements / components / etc.

[0030] Gallium-based liquid metal has high metallic conductivity, thermal conductivity and fluidity at room temperature. As a fluid, it has the characteristics of low viscosity, high surface tension and deformability, and can be widely used in the fields of stretchable electronic products, wearable devices, soft robots, and reconfigurable circuit manufacturing. At the same time, unlike traditional rigid materials (for example, ultra-thin aluminum), which face complex processes, poor flexibility, and electronic system crashes caused by fatigue damage when preparing flexible electronic products, the preparation method of gallium-based liquid metal is simple and has sufficient flexibility, mechanical stability and remodeling, which can improve the durability of electronic equipment. Therefore, with the help of its conductivity and fluidity, it can be introduced into the conductive silver paste system as a self-healing material to enhance the crack self-healing ability of the silver paste and improve the fatigue life, service reliability and stability of flexible electronic devices.

[0031] However, a non-conductive oxide layer is easily formed on the surface of gallium-based liquid metal, and the surface tension is relatively large, so it is difficult to directly introduce it into the conductive silver paste system and enable it to play a specific repair function.

[0032] Based on this, the embodiment of the present disclosure provides a conductive silver paste, which may include the following components: conductive silver powder, gallium-based liquid metal-based composite functional material, organic resin bonding phase, curing agent, organic solvent and auxiliary agent; wherein the weight parts of each component are: the weight part of the conductive silver powder is 55 parts to 75 parts; the weight part of the gallium-based liquid metal-based composite functional material is 5 parts to 25 parts; the weight part of the organic resin bonding phase is 4 parts to 10 parts; the weight part of the curing agent is 1 part to 3 parts; the weight part of the organic solvent is 2 parts to 10 parts; the weight part of the auxiliary agent is 0.1 parts to 10 parts; Gallium-based liquid metal-based composite functional materials include gallium-based liquid metals, conductive polymers and few-layer two-dimensional materials. Gallium-based liquid metals include one or more of gallium, gallium-tin alloys, gallium-indium alloys, gallium-indium-tin alloys or gallium-indium-tin-zinc alloys; conductive polymers include one or more of polypyrrole, polydopamine or polyaniline; few-layer two-dimensional materials include graphene or transition metal carbides.

[0033] Conductive silver powder includes silver nanowires, flaky metallic silver powder and nano-spherical silver powder. The silver nanowires are synthesized by a polyol method.

[0034] The conductive silver paste disclosed in the present invention uses multi-dimensional micro-nano conductive silver powder (including high aspect ratio silver nanowires, flaky metal silver powder and nano-spherical silver particles) to construct a three-dimensional mesh conductive path inside the paste through multi-dimensional interface contact, which effectively improves the conductive stability of the device during flexible deformation and ensures the continuity of electrical connection. By incorporating gallium-based liquid metal-based composite functional materials, the application performance of conductive silver paste in the field of flexible electronic printing has been significantly improved, especially in solving the problems of conductive layer failure and interface mismatch caused by mechanical deformation such as repeated bending / stretching. For example, the gallium-based liquid metal (such as gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy) in the gallium-based liquid metal-based composite functional material acts as a self-flowing crack repair agent. Its high conductivity and self-healing properties can quickly repair cracks when the silver paste layer is bent or stretched, thereby greatly extending the service life of the conductive silver paste. The addition of conductive polymers (such as polypyrrole, polydopamine or polyaniline) and few-layer two-dimensional materials (such as graphene or transition metal carbides) effectively improves the interfacial wettability between liquid metal particles and conductive silver powder and substrate. The high flexibility and good interfacial compatibility of these materials can enhance the matching of rigid and flexible interfaces, which helps to improve the repair effect. At the same time, the conductive polymers and two-dimensional materials in the gallium-based liquid metal-based composite functional materials can also form additional conductive channels, further enhancing the stability and reliability of the conductive network. In addition, the weight of each component is precisely controlled in the present disclosure, so that the conductive silver paste can achieve good adhesion and processing performance while maintaining high conductivity. The synergistic effect of the organic resin binder phase, curing agent and additives ensures that the silver paste can form a dense and uniform conductive layer after curing, so that the final conductive silver paste not only has high bending resistance and strong adhesion, but also shows high reliability, effectively solving the conductive layer failure and interface mismatch problems caused by mechanical deformation (such as cracks) in flexible electronic printing.

[0035] The following is a detailed description of each part of the conductive silver paste in the embodiment of the present disclosure and its specific details: In an exemplary embodiment of the present disclosure, the conductive silver powder may include silver nanowires, flaky metallic silver powder and nano-spherical silver powder, wherein the silver nanowires may be synthesized by a polyol method. The length of the silver nanowire may be 20 μm-50 μm, for example, its length may be 20 μm, 30 μm, 40 μm or 50 μm; the diameter of the silver nanowire may be 30 nm-100 nm, for example, its diameter may be 30 nm, 50 nm, 70 nm, 90 nm or 100 nm; of course, the length and diameter of the silver nanowire may also be other values, which are not listed here. The particle size of the flaky metallic silver powder may be 2.0 μm-8.0 μm, for example, its particle size may be 2.0 μm, 4.0 μm, 6.0 μm or 8.0 μm; of course, the particle size of the flaky metallic silver powder may also be other values, which are not listed here. The particle size of the nano-spherical silver powder may be 5nm-300nm, for example, the particle size may be 5nm, 50nm, 100nm, 200nm or 300nm; of course, the particle size of the nano-spherical silver powder may also be other values, which are not listed here one by one.

[0036] In an exemplary embodiment of the present disclosure, the proportion of silver nanowires in the conductive silver powder may be 2%-15%; for example, the proportion of silver nanowires may be 2%, 5%, 8%, 11%, 13% or 15%. The proportion of nano-spherical silver powder in the conductive silver powder may be 2%-30%; for example, the proportion of nano-spherical silver powder may be 2%, 5%, 10%, 20% or 30%. The rest is flaky metal silver powder.

[0037] The weight of the conductive silver powder can be 55 parts to 75 parts, for example, it can be 55 parts, 60 parts, 70 parts or 75 parts. Of course, the conductive silver powder can also be other parts, which will not be listed here one by one.

[0038] The weight proportion of the gallium-based liquid metal-based composite functional material can be 5-25 parts, for example, it can be 5 parts, 10 parts, 15 parts, 20 parts or 25 parts. Of course, the weight proportion of the gallium-based liquid metal-based composite functional material can also be other proportions, which are not listed here one by one.

[0039] In an exemplary embodiment of the present disclosure, a gallium-based liquid metal-based composite functional material may include a gallium-based liquid metal, a conductive polymer and a few-layer two-dimensional material, wherein the gallium-based liquid metal includes one or more of gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy; the conductive polymer includes one or more of polypyrrole, polydopamine or polyaniline; the few-layer two-dimensional material includes graphene or transition metal carbide.

[0040] In an exemplary embodiment of the present disclosure, the organic resin bonding phase may be one or more of a hydroxyl-terminated polyester resin, an epoxy-modified acrylic resin, and a polyurethane resin. The weight of the organic resin bonding phase may be 4 to 10 parts; for example, it may be 4, 5, 6, 7, 8, 9, or 10 parts, and of course, it may be other parts, which are not listed here.

[0041] In an exemplary embodiment of the present disclosure, the curing agent may be a blocked isocyanate curing agent. The weight of the curing agent may be 1-3 parts; for example, it may be 1 part, 1.5 parts, 2 parts, 2.5 parts or 3 parts, of course, it may be other parts, which are not listed here. The deblocking temperature of the curing agent may be 90°C-130°C, for example, its deblocking temperature may be 90°C, 100°C, 110°C, 120°C or 130°C.

[0042] In an exemplary embodiment of the present disclosure, the organic solvent may include two or more of xylene, alkylbenzene, butyl carbitol, terpineol, N-methylpyrrolidone, butyl carbitol acetate and mixed dibasic esters. The weight of the organic solvent may be 2-10 parts; for example, it may be 2 parts, 4 parts, 6 parts, 8 parts or 10 parts, or other parts, which are not listed here.

[0043] The additives may include modified urea, polysiloxane and thixotropic agent. Among them, the amount of modified urea added may be 0-3% of the total of all components in the conductive silver paste; the amount of polysiloxane added may be 0%-5% of the total of all components in the conductive silver paste; the amount of thixotropic agent added may be 0%-2% of the total of all components in the conductive silver paste. The weight of the additive may be 0.1-10 parts; for example, it may be 0.1 parts, 2 parts, 4 parts, 6 parts, 8 parts or 10 parts, of course, it may also be other parts, which will not be listed here.

[0044] The present disclosure also provides a method for preparing a conductive silver paste, which is used to prepare the conductive silver paste in any of the above embodiments. Figure 1 As shown, the preparation method includes steps S110 to S160, wherein: Step S110, preparing a gallium-based liquid metal-based composite functional material, wherein the gallium-based liquid metal-based composite functional material includes a gallium-based liquid metal, a conductive polymer, and a few-layer two-dimensional material, wherein the gallium-based liquid metal includes one or more of gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy, or gallium-indium-tin-zinc alloy; the conductive polymer includes one or more of polypyrrole, polydopamine, or polyaniline; and the few-layer two-dimensional material includes graphene or transition metal carbide; Step S120, preparing a silver nanowire dispersion by a polyol synthesis method; Step S130, weighing an organic resin binder phase and an organic solvent by weight, adding them to the silver nanowire dispersion, and stirring them to a homogeneous state to form an organic carrier; Step S140, adding gallium-based liquid metal-based composite functional materials, flaky metal silver powder and nano-spherical silver powder into the organic carrier in small amounts and continuously stirring in a planetary mixer to prepare a uniform slurry; Step S150, adding an auxiliary agent and a curing agent to the uniform slurry, and continuing to stir to adjust the slurry viscosity and thixotropic properties to form an initial conductive silver paste; Step S160, adjusting the fineness of the initial conductive silver paste by a three-roll grinder, and obtaining the target conductive silver paste after double-layer filtration.

[0045] The preparation method of the conductive silver paste disclosed in the present invention significantly improves the application performance of the conductive silver paste in the field of flexible electronic printing by incorporating gallium-based liquid metal-based composite functional materials, and has made breakthrough progress in solving the problems of conductive layer failure and interface mismatch caused by mechanical deformation such as repeated bending / stretching. For example, the gallium-based liquid metal (such as gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy) in the gallium-based liquid metal-based composite functional material is used as a self-flowing crack repair agent. Its high conductivity and self-healing properties can quickly repair cracks when the silver paste layer is bent or stretched, thereby greatly extending the service life of the conductive silver paste. The addition of conductive polymers (such as polypyrrole, polydopamine or polyaniline) and few-layer two-dimensional materials (such as graphene or transition metal carbides) effectively improves the interface wettability between liquid metal particles and conductive silver powder and substrates. The high flexibility and good interface compatibility of these materials can enhance the matching of rigid and flexible interfaces, which helps to improve the repair effect. At the same time, the conductive polymers and two-dimensional materials in the gallium-based liquid metal-based composite functional materials can also form additional conductive channels, which helps to enhance the stability and reliability of the conductive network. In addition, by precisely controlling the weight of each component in the present disclosure, the conductive silver paste can achieve good adhesion and processing performance while maintaining high conductivity. The synergistic effect of the organic resin adhesive phase, curing agent and additives ensures that the silver paste can form a dense and uniform conductive layer after curing, so that the final conductive silver paste not only has high bending resistance and strong adhesion, but also shows high reliability, effectively solving the conductive layer failure and interface mismatch problems caused by mechanical deformation (such as cracks) in flexible electronic printing.

[0046] In an exemplary embodiment of the present disclosure, preparing a gallium-based liquid metal-based composite functional material (ie, step S110) may include steps S210 to S250, wherein: Step S210, weighing gallium-based liquid metal by weight, adding it into a special ultrasonic crushing vessel containing 10 ml of sodium dodecylbenzene sulfonate aqueous solution, and ultrasonic crushing it at a constant temperature of 20° C. to form a suspension I.

[0047] In some embodiments of the present disclosure, the gallium-based liquid metal may be one of gallium indium, gallium tin, gallium indium tin, and gallium indium tin zinc. Sodium dodecylbenzene sulfonate may be used as a dopant and stabilizer, and the amount of sodium dodecylbenzene sulfonate and the polypyrrole to be added subsequently is added at a molar ratio of sodium dodecylbenzene sulfonate / polypyrrole of 0.2-0.8:1.

[0048] In some embodiments of the present disclosure, the duration of ultrasonic crushing can be 5 minutes to 10 minutes, for example, the duration of ultrasonic crushing can be 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes; of course, ultrasonic crushing can also be other durations, which are not listed here. The ultrasonic amplitude of the ultrasonic crushing process is: 60%; the ultrasonic time interval is 2 seconds or 3 seconds.

[0049] Step S220, weigh Ti3AlC2 powder and lithium fluoride powder by weight and add them to a hydrochloric acid solution, and use a lithium fluoride-hydrochloric acid etching process and an ultrasonic stripping process to obtain a dark green few-layer Ti3C2T x The nanosheets 1 are dispersed in an aqueous solution to serve as the suspension 2. In the present disclosure, the few-layer Ti3C2T x The scanning electron microscope image of nanosheet 1 is shown in Figure 2 shown.

[0050] In some embodiments of the present disclosure, the hydrochloric acid in the lithium fluoride-hydrochloric acid etching process may be a 6 mol / L hydrochloric acid solution. During the ultrasonic stripping process, the beaker may be placed in an ice bath to reduce the ultrasonic temperature, and Ar may be introduced to prevent Ti3C2T x Oxidation.

[0051] Step S230, mixing the suspension 1 and the suspension 2 by weight and ultrasonicating them for 10 minutes, based on the negatively charged Ti3C2T x The electrostatic repulsion between the liquid metal and the gallium-based liquid metal results in a uniform mixed solution of gallium-based liquid metal and two-dimensional material.

[0052] Step S240, adding the reactant conductive polymer monomer-polypyrrole to the mixed solution, mixing and stirring for 2min-5min, adding the oxidant ferric chloride hexahydrate, and fully reacting for 1h to obtain a black suspension.

[0053] In some embodiments of the present disclosure, ferric chloride hexahydrate (ie, FeCl 3 ·6H 2 O) is added in an amount such that the molar ratio of the oxidant to the polypyrrole is 1:1.

[0054] Step S250, washing, vacuum filtering and vacuum drying the black suspension for multiple times to obtain a gallium-based liquid metal-based composite functional material.

[0055] In some embodiments of the present disclosure, the multiple washings in step S250 include: washing with deionized water and ethanol three times respectively. In the present disclosure, the scanning electron microscope image of the gallium-based liquid metal-based composite functional material 2 obtained after drying is as follows: Figure 3 At the same time, the scanning electron microscope images of the important components (for example, gallium (Ga), tin (Sn), titanium (Ti) and nitrogen (N)) in the gallium-based liquid metal-based composite functional material 2 are shown in FIG. Figure 4-Figure 7 As shown, it should be noted that Figure 4-Figure 7 The colored area in the middle is the element distribution area corresponding to the figure. The X-ray photoelectron spectrum of gallium-based liquid metal-based composite functional material 2 is shown in Figure 8 shown.

[0056] The preparation method of the liquid metal-based composite functional material disclosed in the present invention is simple. A highly conductive and flexible self-healing agent is successfully obtained through electrostatic self-assembly. The material has good interface wettability and adhesion with silver paste and substrate, thus ensuring its application reliability in the field of flexible electronics.

[0057] In an exemplary embodiment of the present disclosure, the preparation of a silver nanowire dispersion by a polyol synthesis method (i.e., step S120) may include: weighing 0.3 parts of sodium chloride, 1.2 parts of silver nitrate, and 1.2 parts of polyvinyl pyrrolidone by weight, and adding the weighed sodium chloride, silver nitrate, and polyvinyl pyrrolidone to a beaker in a reactor containing ethylene glycol, and performing microwave reaction at 140° C. to prepare a silver nanowire dispersion. The method for preparing a silver nanowire dispersion is a polyol method, and after the reaction, the beaker can be quickly placed in ice to cool, and acetone can be added and centrifuged several times to obtain a silver nanowire dispersion.

[0058] In step S130, the organic resin binder phase and the organic solvent are weighed by weight and added to the prepared silver nanowire dispersion, and stirred at a constant temperature in a high-speed dispersing axe until the mixture is homogeneous. In this process, the speed of the high-speed dispersing axe is 1000 rpm-5000 rpm, the dispersing temperature is controlled at 55°C-85°C, the stirring and mixing time is 10 minutes-30 minutes; the revolution speed of the agitator is 1000 rpm-2200 rpm, and the rotation speed of the agitator is 700 rpm-1400 rpm.

[0059] In step S160, the spacing between adjacent rollers in the three-roll mill is 2 μm-20 μm, and the rotation speed of the three-roll mill is 300 rpm-500 rpm. The curing temperature of the target conductive silver paste prepared in the present disclosure is 90° C.-130° C., and the curing time is 10 min-20 min.

[0060] The preparation method of the conductive silver paste described in the exemplary embodiment of the present disclosure will be further explained and illustrated in conjunction with specific embodiments below.

[0061] Example 1 The raw materials include the following components by weight: 25 parts of gallium-based liquid metal-based composite functional materials, 55 parts of conductive silver powder, 4 parts of organic resin bonding phase, 1 part of blocked isocyanate curing agent, 5 parts of organic solvent, and 10 parts of auxiliary agent. Among them, the gallium-based liquid metal-based composite functional material is prepared by self-assembly of gallium-based liquid metal, polypyrrole and transition metal carbide. The conductive silver powder includes 30 parts of flaky metal silver powder with a D50 of 7.5 μm (D50 is the particle size corresponding to the cumulative particle size distribution percentage of the sample reaching 50%); 15 parts of spherical ultrafine silver powder with a D50 of 200 nm and 10 parts of self-made silver nanowires (length 30 μm, diameter 50 nm); the organic resin bonding phase includes 1 part of hydroxyl-terminated polyester resin and 3 parts of epoxy-modified acrylic resin; the blocked curing agent is HDI (aliphatic polyisocyanate) with a deblocking temperature of 90°C; the organic solvent includes 2 parts of butyl carbitol, 1 part of xylene, and 2 parts of mixed dibasic esters; the additives include 3 parts of modified urea, 5 parts of polysiloxane, and 2 parts of thixotropic agent.

[0062] The specific preparation process is as follows: Preparation of gallium-based liquid metal-based composite functional materials: 200 mg of gallium-tin alloy liquid metal and 10 mL of sodium dodecylbenzene sulfonate (the molar ratio of sodium dodecylbenzene sulfonate / polypyrrole is 0.5:1) are added to a special ultrasonic crushing vessel (e.g., a flask) filled with deionized water, and ultrasonic crushed at a constant temperature of 20°C for 5 minutes to obtain a gallium-tin nanoparticle dispersion (i.e., suspension 1). Argon gas can be used to remove the air in the flask.

[0063] Ti3AlC2 powder and lithium fluoride powder were weighed by weight and added into hydrochloric acid solution. Dark green few-layer Ti3C2T x A dispersed aqueous solution of nanosheets 1 (i.e., suspension 2); mixing suspension 1 and suspension 2 by weight and ultrasonically for 10 minutes to obtain a mixed solution 1; adding 40 μL of polypyrrole to the mixed solution 1 to obtain a mixed solution 2, and stirring for 5 minutes; dissolving the corresponding mass of the oxidant in 2 mL of deionized water according to a molar ratio of oxidant to polypyrrole (i.e., FeCl3·6H2O / Py) of 1:1, and then quickly dropping it into the mixed solution 2, and fully reacting for 1 hour to obtain a black flocculent mixed solution; after multiple washings, vacuum filtration and vacuum drying, a gallium-based liquid metal-based composite functional material is obtained.

[0064] Preparation of silver nanowires: Using microwave-assisted heating technology, 200 mg of silver nitrate was used as the silver source, 800 mg of polyvinyl pyrrolidone was used as the stabilizer and protective agent, and 200 mg of sodium chloride was used as the control agent. After adding an appropriate amount of ethylene glycol to microwave reaction (temperature 140°C, frequency 400W, time 4min), a high-purity silver nanowire dispersion was prepared. After the reaction was completed, the suspension was cooled in ice cubes and added to a centrifuge tube containing acetone for high-speed centrifugation (speed: 2000rpm) to retain the silver nanowires in the lower layer until the final high-concentration silver nanowire dispersion was obtained.

[0065] Preparation of organic carrier: 1 part of hydroxyl-terminated polyester resin, 3 parts of epoxy-modified acrylic resin and 5 parts of organic solvent (2 parts of butyl carbitol, 1 part of xylene and 2 parts of mixed dibasic ester) were added to the above-mentioned high-concentration silver nanowire dispersion, and mixed and stirred at 1000 rpm in a high-speed dispersion kettle at 80°C until homogeneous.

[0066] Preparation of conductive silver paste: add 25 parts of gallium-based liquid metal-based composite functional materials, 30 parts of lamellar metal silver powder and 15 parts of nano-spherical silver powder in small amounts and multiple times to a constant temperature high-speed dispersing kettle containing an organic carrier, stir at high speed for 20 minutes, transfer to a planetary stirring degassing machine and continue stirring for 5 minutes; continue to add 3 parts of modified urea, 5 parts of polysiloxane and 2 parts of thixotropic agent, degas and stir for 10 minutes, and then roll the mixed slurry through a three-roll mill. The three rollers in the three-roll mill can be defined as the first roller body, the second roller body and the third roller body, respectively. The spacing between the first roller body and the second roller body can be adjusted to 20μm, and the same The spacing between the second roller and the third roller is adjusted to 15 μm, and the mixed slurry is preliminarily rolled; the spacing between the first roller and the second roller is adjusted to 15 μm, and the spacing between the second roller and the third roller is adjusted to 7 μm, and the mixed slurry that has been preliminarily rolled is secondarily rolled; the spacing between the first roller and the second roller is adjusted to 7 μm, and the spacing between the second roller and the third roller is adjusted to 3 μm, and the mixed slurry that has been secondarily rolled is thirdly rolled to make the slurry fineness less than 5 μm, and finally, after passing through a double filtration system of 500 mesh-300 mesh, a conductive silver paste is prepared.

[0067] The specific implementation process of Examples 2 to 5 and Comparative Example 1 is similar to that of Example 1, except that the components or weight portions of the components used are different. Therefore, the specific implementation process of Examples 2 to 5 and Comparative Example 1 is not described in detail here. The specific components and weight portions of Examples 2 to 5 and Comparative Example 1 are shown in Table 1 below.

[0068] Table 1 Specific components and weight parts of Examples 2 to 5 and Comparative Example 1

[0069] In the present disclosure, the performance test of the conductive silver paste prepared in each embodiment and comparative example is also carried out. Specifically, the conductive silver paste prepared in each embodiment and comparative example can be screen printed on a polyethylene terephthalate film (screen printing area: 1×1 cm) through a 350 mesh screen, and the printed sample is placed in a 90°C constant temperature drying oven for drying for 20 minutes, and then taken out for performance testing. The performance test results of all embodiments and comparative examples are shown in Table 2.

[0070] Table 2 Performance parameters of samples prepared in various embodiments and comparative examples

[0071] It should be noted that in the present disclosure, the bending resistance of the conductive silver paste is mainly affected by the weight of the conductive silver powder and the gallium-based liquid metal-based composite functional material, and the other components have little effect on the bending resistance of the conductive silver paste.

[0072] By comparing Examples 1 to 5 with Comparative Example 1, it can be seen that the bending resistance of the conductive silver paste using the gallium-based liquid metal-based composite functional material as the conductive functional phase is significantly better than that of the conductive silver paste not using the gallium-based liquid metal-based composite functional material as the conductive functional phase. This is because: the gallium-based liquid metal-based composite functional material in the present disclosure selects a graphene-like layered 2D material (Ti3C2T x ) as a framework material, has the characteristics of high conductivity, high flexibility and large specific surface area. With its electronegativity and hydrogen bonding, it can realize the effective adsorption and in-situ polymerization self-assembly of pyrrole monomers to prepare highly flexible "liquid metal-polypyrrole-Ti3C2T x "Composite materials can improve the printing pattern resolution of liquid metal-based conductive silver paste, while giving full play to its crack repair ability in the conductive silver paste, thereby greatly improving the bending resistance of the conductive silver paste.

[0073] At the same time, the conductive silver paste prepared in the present disclosure uses gallium-based liquid metal-based composite functional materials and multi-dimensional micro-nano mixed conductive silver powder as the conductive functional phase, so that the highly flaky metal silver powder, nano-spherical silver powder, silver nanowires and liquid metal-based composite functional materials are in direct contact to form a smooth three-dimensional conductive network, which can effectively reduce the resistivity of the conductive silver paste, and show a small resistance change rate after bending, and have excellent bending resistance; adjust the conductive functional phase ratio so that as the proportion of gallium-based liquid metal-based composite functional materials increases, the bending resistance of the conductive silver paste generally shows an increasing trend. At the same time, based on the formula analysis of the embodiments and comparative examples, the optimal ratio of conductive silver powder, gallium-based liquid metal-based composite functional materials, organic resin bonding phase, curing agent, auxiliary agent and organic solvent can be obtained. In summary, the conductive silver paste prepared in the present disclosure has high reliability, good printing adaptability on flexible substrates, and after rapid curing under low temperature conditions of 90°C, the conductive silver paste has excellent adhesion, low square resistance and high bending resistance.

[0074] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.

Claims

1. A conductive silver paste, characterized in that: The conductive silver paste comprises the following components: conductive silver powder, gallium-based liquid metal-based composite functional material, organic resin bonding phase, curing agent, organic solvent and auxiliary agent, wherein: the weight portion of the conductive silver powder is 55-75 parts; the weight portion of the gallium-based liquid metal-based composite functional material is 5-25 parts; the weight portion of the organic resin bonding phase is 4-10 parts; the weight portion of the curing agent is 1-3 parts; the weight portion of the organic solvent is 2-10 parts; the weight portion of the auxiliary agent is 0.1-10 parts; The gallium-based liquid metal-based composite functional material includes gallium-based liquid metal, conductive polymer and few-layer two-dimensional material, wherein the gallium-based liquid metal includes one or more of gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy; the conductive polymer includes one or more of polypyrrole, polydopamine or polyaniline; the few-layer two-dimensional material includes graphene or transition metal carbide.

2. The conductive silver paste according to claim 1, characterized in that: The conductive silver powder comprises silver nanowires, flaky metal silver powder and nano-spherical silver powder, and the silver nanowires are synthesized by a polyol method.

3. The conductive silver paste according to claim 1, characterized in that: The organic resin bonding phase is one or more of a hydroxyl-terminated polyester resin, an epoxy-modified acrylic resin and a polyurethane resin.

4. The conductive silver paste according to claim 1, characterized in that: The curing agent is a blocked isocyanate curing agent.

5. The conductive silver paste according to claim 1, characterized in that: The organic solvent includes two or more of xylene, alkylbenzene, butyl carbitol, terpineol, N-methylpyrrolidone, butyl carbitol acetate and mixed dibasic esters.

6. The conductive silver paste according to claim 1, characterized in that: The auxiliary agent includes two or three of modified urea, polysiloxane and thixotropic agent.

7. A method for preparing a conductive silver paste, for preparing the conductive silver paste according to any one of claims 1 to 6, characterized in that: The preparation method comprises: Prepare a gallium-based liquid metal-based composite functional material, wherein the gallium-based liquid metal-based composite functional material comprises a gallium-based liquid metal, a conductive polymer and a few-layer two-dimensional material, wherein the gallium-based liquid metal comprises one or more of gallium, gallium-tin alloy, gallium-indium alloy, gallium-indium-tin alloy or gallium-indium-tin-zinc alloy; the conductive polymer comprises one or more of polypyrrole, polydopamine or polyaniline; the few-layer two-dimensional material comprises graphene or transition metal carbide; The silver nanowire dispersion was prepared by polyol synthesis method; Weighing an organic resin binder phase and an organic solvent by weight, adding them to the silver nanowire dispersion, and stirring until a homogeneous state to form an organic carrier; Adding the gallium-based liquid metal-based composite functional material, flaky metal silver powder and nano-spherical silver powder into the organic carrier in small amounts and repeatedly, and continuing to stir in a planetary mixer to prepare a uniform slurry; Adding an auxiliary agent and a curing agent to the uniform slurry, and continuing stirring to adjust the viscosity and thixotropic properties of the slurry to form an initial conductive silver slurry; The fineness of the initial conductive silver paste is adjusted by a three-roll mill, and the target conductive silver paste is obtained after double-layer filtration.

8. The preparation method according to claim 7, characterized in that: The method for preparing the gallium-based liquid metal-based composite functional material comprises: Weigh gallium-based liquid metal by weight and add it into a special ultrasonic crushing vessel containing 10 ml of sodium dodecylbenzene sulfonate aqueous solution, and crush it by ultrasonic at a constant temperature of 20° C. to form a suspension 1; Ti3AlC2 powder and lithium fluoride powder were weighed by weight and added into hydrochloric acid solution. The dark green few-layer Ti3C2T x A dispersed aqueous solution of nanosheets is used as suspension II; The suspension 1 and the suspension 2 were mixed by weight and ultrasonicated for 10 minutes. x The electrostatic repulsion between the liquid metal and the gallium-based liquid metal results in a uniform mixed solution of the two-dimensional material. Adding the reactant conductive polymer monomer-polypyrrole to the mixed solution, mixing and stirring, adding the oxidant ferric chloride hexahydrate, and fully reacting for 1 hour to obtain a black suspension; The black suspension is washed multiple times, vacuum filtered and vacuum dried to obtain a gallium-based liquid metal-based composite functional material.

9. The preparation method according to claim 7, characterized in that: The polyol synthesis method is used to prepare the silver nanowire dispersion, comprising: 0.3 parts of sodium chloride, 1.2 parts of silver nitrate and 1.2 parts of polyvinyl pyrrolidone were added into a reaction kettle containing ethylene glycol, and a silver nanowire dispersion was prepared by microwave reaction at 140°C.

10. The preparation method according to claim 7, characterized in that: The curing agent is a blocked isocyanate curing agent; the organic solvent includes two or more of xylene, alkylbenzene, butyl carbitol, terpineol, N-methylpyrrolidone, butyl carbitol acetate and mixed dibasic esters; the auxiliary agent includes two or three of modified urea, polysiloxane and thixotropic agent; the organic resin bonding phase is one or more of hydroxyl-terminated polyester resin, epoxy-modified acrylic resin and polyurethane resin.

Citation Information

Patent Citations

  • Colored conductive paste, preparation method thereof and electronic device

    CN111863308A

  • Preparation method of hollow silver nanotube conductive paste

    CN113539548A

  • Conductive silver paste and preparation method thereof

    CN119274846A

  • Paste material, wiring member formed from the paste material, and electronic device including the wiring member

    US20180148584A1

  • Conductive material, method for manufacturing the same, and electronic device

    US20220336120A1

Cited By

  • Metal nanoparticle composite conductive liquid and preparation method thereof

    CN121583603A